Perkembangan Model Pembelajaran Berbasis Permainan Sirkuit Dalam Meningkatkan Motorik Halus Anak Usia 4-6 Tahun - Putri Elisabeth Kolly; Elsa Mariana Pian; Oktifina Loni Sabila; Sifra Yulti Nisipeni; Desi Katarina Saepito; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Fine motor skills are an important aspect of early childhood development through active and enjoyable learning. This study aims to analyze the effect of a circuit-based learning model on the fine motor skills of children aged 4–6 years at Efrata Preschool. The study used a quantitative approach with an ex post facto design. The sample size was 20 children aged 4–6 years, selected using a total sampling technique. Data collection was conducted using a questionnaire consisting of a circuit-based learning model scale and a child's fine motor skills scale that met validity and reliability tests. The data were analyzed using simple linear regression analysis using SPSS version 25.0. The results showed that the circuit-based learning model had a positive and significant effect on the fine motor skills of children aged 4–6 years (p = 0.003 < 0.05). The coefficient of determination (R Square) of 0.381 indicates that the circuit-based learning model contributed 38.1% to children's fine motor development, while the remaining 61.9% was influenced by factors outside the study. Thus, implementing a circuit-based game-based learning model in a structured and consistent manner can be an alternative learning method to optimize fine motor development in early childhood education (PAUD) units.